The K-Pop Fans Perception Over a Cancel Culture Phenomenon - Putri Febrianti, Nadhira; Ahmad, Zalinah; Osman, Sharifuzah; Nimatu Rohmah , Ainun (UNIVERSITAS SARI MUTIARA INDONESIA, 2023)
This study examines the perception of K-pop fans towards a cancel culture phenomenon that is happening. The background of this thesis begins when cancel culture emerges and has been used against certain individual or groups of people as an act of boycott. This cancel culture is also happening within K-pop communities as an act of cyberbullying and has been used as a common term in social media platforms. This study uses qualitative as a research method with phenomenological approach to gain deeper information from the respondent. With semi-structured interview as a data collection method, this study expected to give a different experience from the respondent regarding cancel culture. As the results, six respondents have similar perception over a cancel culture phenomenon as most of them agree that cancel culture is inclined to the negative side. Although overall, cancel culture has both positive and negative sides. This research also finds that most respondents never experience the cancel culture phenomenon themselves, but someone that they know in K-pop community has experienced the impact of cancel culture. Therefore, hopefully this study can be used as an awareness from using social media platforms. It will also be able to consider a regulation to make social media platforms a safe space for people to use in the future.